Effect of citric acid and acetic acid on the performance of broilers (Journal of the Bangladesh Agricultural University, 2010)
An experiment was conducted with commercial broilers to investigate the effects of feeding citric acid, acetic acid and their combination on their performance and to determine the economic competence of using citric acid and acetic acid in broiler rations. A total number of 108 one day old straight run broiler chicks were distributed to four dietary treatments i.e. 0 % citric or acetic acid (A), 0.5% citric acid (B), 0.5% acetic acid (C) and their combinations 0.5% citric acid and 0.5% acetic acid (D). The birds were reared in cages. Body weight gains, feed conversion ratio (FCR), mortality, dressing yield and carcass characteristics were recorded. The performance showed significant increase in body weight gain (P